HUMANISTIC LITERATION DIAGNOSIS IN CONSTRUCTIVE LEARNING MODEL IN ELEMENTARY SCHOOL STUDENTS IN BULELENG REGENCY (International Conference on Elementary Education, 2018)
This research is Ex Post Facto research. This study aims to determine and analyze the magnitude of the determination of Humanistic Literacy in constructivist learning models in elementary school students of Buleleng Regency. The study population was 100 elementary school students of Buleleng Regency. Data collection was carried out with a closed questionnaire. Data were analyzed by applying statistical formulas with product moment techniques and partial correlations. The results of data analysis show that there is a determination of Humanistic Literacy in constructivist learning models in Buleleng Regency elementary school students by 44%.